Production potential of bio-energy crops in multifunctional agriculture and rural development - S. Dželetović, Željko; Lj. Mihailović, Nevena; D. Dražić, Gordana (Economics of Agriculture, 2010)
Bio-energy crops are grown with the specifc purpose of utilizing their parts or the whole plant mass for the production of liquid or solid fuels, as an alternative to fossil fuels. The use of traditional bioenergy crops (straw of cereals and wood mass) and common feld crops (for ethanol and bio-diesel) are considered. Promising for such utilization are also various species of annual and perennial grasses, among which miscanthus (Miscanthus×giganteus Greef et Deu.) is especially recognized as a source of good quality biomass. Only the intensive use of the existing and new energy crops could bring about a greater multi-functionality of agriculture, as well as comparative cost/beneft stability of agriculture and encourage the rural development.